Evaluations of healthcare delivery models in Australia: a scoping review protocol. Issue 1 (25th January 2020) - Roseleur, Jacqueline; Partington, Andrew; Karnon, Jonathan
ABSTRACT: Objective: The aim of this review is to identify and describe the evidence base of published primary, comparative healthcare delivery model evaluations that require the employment of additional healthcare practitioners undertaken in Australia. Introduction: In Australia, formal processes are utilized in assessing the value of new pharmaceuticals and medical services, which inform decisions on whether to list new items on the Pharmaceutical Benefits Schedule and Medicare Benefits Schedule, respectively. There are no formal processes to aid in decision making on the funding of new, evaluated healthcare delivery models. This imbalance undervalues the available evidence on healthcare delivery models, leading to the sub-optimal allocation of resources between new health technologies and new healthcare delivery models within the Australian health system. Inclusion criteria: Eligible studies will evaluate healthcare delivery models that require the employment of additional healthcare practitioners (either to replace existing practitioners of another type or to provide new services). Studies must include a comparator to evaluate a condition of interest being treated using alternative healthcare delivery models, or no treatment, and will involve observation of outcomes over a similar period of time. Studies in any Australian setting will be included. Interventions aimed at primary preventions will be excluded. Methods: PubMed, Embase and CINAHL will be searched for articles published from 2008. One reviewer will review titles, and then two reviewers will independently review abstracts to identify eligible studies. One reviewer will extract data on study characteristics and design. The results of the data extraction will be presented in a table with examples of case studies.